2019
DOI: 10.3389/fimmu.2019.00557
|View full text |Cite
|
Sign up to set email alerts
|

Mesenteric Lymphatic Alterations Observed During DSS Induced Intestinal Inflammation Are Driven in a TLR4-PAMP/DAMP Discriminative Manner

Abstract: Background: Inflammatory bowel disease (IBD) is characterized by both acute and chronic phase inflammation of the gastro-intestinal (GI) tract that affect a large and growing number of people worldwide with little to no effective treatments. This is in part due to the lack of understanding of the disease pathogenesis and also the currently poorly described involvement of other systems such as the lymphatics. During DSS induced colitis, mice also develop a severe inflammation of terminal ileum with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 57 publications
0
22
0
Order By: Relevance
“…A shift in balance of LPS-TLR4 signalling from unbiased NF-κB/IRF3 toward the more anti-inflammatory IRF3 cascade is a known feature in regulating tolerance to LPS 32 . The role of this balance shift in chronic diseases such as: inflammatory bowel disease, amyotrophic Lateral Sclerosis, liver disease, or rheumatic diseases, is still poorly understood, but creates an avenue of research for future investigation especially in diseases where there is known involvement of bacterial products and/or NF-κB/IRF3 signalling 15 , 33 35 . In the expanding realm of the microbiota and its involvement in disease progression, we theorise that this discriminative capacity may be defunct in certain patient cohorts and infections.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A shift in balance of LPS-TLR4 signalling from unbiased NF-κB/IRF3 toward the more anti-inflammatory IRF3 cascade is a known feature in regulating tolerance to LPS 32 . The role of this balance shift in chronic diseases such as: inflammatory bowel disease, amyotrophic Lateral Sclerosis, liver disease, or rheumatic diseases, is still poorly understood, but creates an avenue of research for future investigation especially in diseases where there is known involvement of bacterial products and/or NF-κB/IRF3 signalling 15 , 33 35 . In the expanding realm of the microbiota and its involvement in disease progression, we theorise that this discriminative capacity may be defunct in certain patient cohorts and infections.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple analyses were performed using a one-way Anova with post-hoc Tukeys test where indicated. * P < 0.05, ** P < 0.01, *** P < 0.001, **** P < 0.0001 15 .…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…The importance of the balancing role of TLR4 in intestinal injury and repair is also reported by Yun-Jie and colleagues, who found that moderate activation of TLR4 signaling both promotes inflammation and repairs the intestinal epithelium in DSS-induced colitis and radiation damage [ 124 ]. TLR4-mediated signaling is important for the recruitment of immune cells to the site of inflammation, promoting reparative mechanisms, but can be described as a double-edged sword, as aberrant stimulation can induce chronic inflammation and mesenteric lymphatic alterations in a TLR4-PAMP (pathogen-associated molecular patterns)/DAMP (-associated molecular patterns) discriminative manner [ 125 ]. The observation that reduced lymphangiogenesis improves DSS-induced phenotype implies that the restoration of lymphatic function to a “normal” phenotype, significantly aids the repair of DSS-induced disease activity, which is achieved through TLR4 blockade with C34 [ 125 ].…”
Section: Molecular Mediators Of Lymphangiogenesis In Ibdmentioning
confidence: 99%
“…TLR4-mediated signaling is important for the recruitment of immune cells to the site of inflammation, promoting reparative mechanisms, but can be described as a double-edged sword, as aberrant stimulation can induce chronic inflammation and mesenteric lymphatic alterations in a TLR4-PAMP (pathogen-associated molecular patterns)/DAMP (-associated molecular patterns) discriminative manner [ 125 ]. The observation that reduced lymphangiogenesis improves DSS-induced phenotype implies that the restoration of lymphatic function to a “normal” phenotype, significantly aids the repair of DSS-induced disease activity, which is achieved through TLR4 blockade with C34 [ 125 ]. This apparent contradiction of the general observation that increased lymphangiogenesis improves IBD implies that a balance is required in the therapeutic induction of lymphangiogenesis to arrive at a maximum benefit.…”
Section: Molecular Mediators Of Lymphangiogenesis In Ibdmentioning
confidence: 99%